Evolution and protein interactions of LEUNIG and SEUSS homologs across land plants - Garrecht, Julian; Rössner, Clemens; Sreechakram, Vishnu Narayanan Suma; Li, Quiwei; Braun, Sigurd; Golz, John; Becker, Annette; Justus Liebig University Giessen (My University, 2025)
The evolution of land plants has involved significant restructuring and expansion of gene networks responsible for developmental processes, leading to the emergence of new expression patterns and gene activities. The transcriptional co-regulators LUG (LEUNIG) and SEU (SEUSS) play crucial roles in Arabidopsis thaliana's sexual reproduction, participating in various development processes required for forming angiosperm-specific features. While LUG and SEU have existed for at least 500 million years, their exact phylogenetic relationship, and when they became protein interaction partners remain unclear. We carried out phylogeny reconstruction, protein domain analysis and comparative transcriptome analysis to elucidate the evolutionary dynamics of the LUG and SEU gene homologs across land plants, revealing insights into protein interactions and lineage-specific adaptations. LUG and SEU proteins from diverse land plant lineages interact via the same protein regions and these domains are also found in Zygnematophyceae, suggesting that LUG-SEU dimerization predates land plants but is not found in other Streptophyte algae lineages. Our findings suggest that while physical interactions are conserved among the LUG/SEU proteins in land plants and beyond, there exist lineage-specific differences in expression patterns and domain organization, which may contribute to functional diversification of LUG and SEU during evolution. Further research is warranted to elucidate the structural and functional implications of these variations across diverse plant lineages.
Keywords: plant evolution; evolution of transcriptional regulators; ddc:580